Multisensory Intervention for Preterm Infants Improves Sucking Organization. (April 2015) - Medoff-Cooper, Barbara; Rankin, Kristin; Li, Zhuoying; Liu, Li; White-Traut, Rosemary; Dowling, Donna
<x xml:space="preserve">Abstract</x> Background Premature infants are at risk for difficulties in feeding, social interaction, and growth. Many premature infants exhibit a lower capacity for self-regulation, resulting in less behavioral alertness and hypersensitivity to stimulation. Feeding is critically important because it is a primary factor for infant growth and a major concern for both parents and clinicians. Purpose The aim of this randomized controlled trial was to evaluate sucking organization in premature infants following a preterm infant multisensory intervention, the Auditory, Tactile, Visual, and Vestibular (ATVV) intervention. Methods: A convenience sample of 183 healthy premature infants born 29-34 weeks postmenstrual age (PMA) enrolled. Sucking organization was measured at baseline, then weekly, during the infant's hospital stay. Results: A quadratic trend was observed for number of sucks, sucks per burst, and maturity index with the intervention group increasing significantly faster by day 7 (model estimates for group × day: β= 13.69, P < .01; β = 1.16, P < .01; and β= 0.12, P < .05, respectively). Sucking pressure increased linearly over time, with significant between-group differences at day 14 (β= 45.66, P < .01). Implications for Practice: The ATVV infants exhibited improved sucking organization during hospitalization, suggesting that the ATVV intervention improves maturation of oral feeding. Implications for Research: Further research that includes 2 or more tests, delivered the same day and/or over consecutive days, will provide researchers and clinicians a more sensitive indicator of maturational changes in feeding behaviors.